The education organization in the Federal Territory of Iguazu in 1946; Contributions of Laudímia Trotta - Lemiechek, Lucimara; Castanha, André Paulo (Educere et Educare, 2000)
<!–[if gte mso 9]> 800x600 <![endif]–> It has been analyzed the situation of education in the Federal Territory of Iguazu as well the role played by Laudimia Trona in the organization and restructuration of education of the Territory between April and September of 1946. Before a very precariousness situation we wonder: which were the strategies used by her and her team in order to adjust the education of the Territory to the educational scene of that time? Although her work has happened in a very short period of time, her contribution for the education in a region where education until that moment had been abandoned by the government is very important. Being part of a project of national scope idealized by the Governor of Getulio Vargas known as the March to the West, the creation of Territory has boosted the West and South west of Parana State and West of Santa Catarina State reaching affecting positively their thousands of settlers pointing the regions for the progress and visibility. However, her short time (1943-1946) made the region ended up back to the stagnation and oblivion as in the past. <!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>